HUBUNGAN MENTAL THOUGHNESS TERHADAP COMPETITIVE ANXIETY PADA ATLET KARATE BANDUNG KARATE CLUB (BKC) KOTA PEKANBARU - Misriani Misriani; Agus Sulastio; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Competitive anxiety is a negative disorder that arises suddenly when athletes feel preasure, especially in competition. The negative attitude cause by competitive anxiety is a feeling of anxiety, cold sweat and unfocused. This is also triggered by a lack of mental thoughness or positive abilities when facing pressure in a macth, anxiety at a high levelmakes the athlete’s performance decrease, therefore mental thoughness is needed to deal with this anxiety. This study aims to see wheter there is a relatiosnship between mental thoughness and competitive anxiety in karate athletes from bandung karate club (BKC) pekanbaru city. The method in this research is a quantitative research method with a population and sample of 15 karate athletes. The measuring instrument use is the mental thoughness scale and the competitive anxiety scale, which were analyzed using the SPSS 26 person product moment relation formula. The result of this study indicate that there is a negative relationship between mental thoughness and competitive anxiety in karate athletes at bandung karate club (BKC) pekanbaru city (r=-455). The higher of mental thoughness attitude, the lower of competitive anxiety behavior in karate athletes from bandung karate club (BKC) pekanbaru city.Key Words: Mental Thoughness, Competitive Anxiety, Karate Athletes